Profil Berpikir Kritis Siswa Smp Dalam Pemecahan Masalah Matematika Ditinjau Dari Gaya Kognitif - Elfa Puspita; Sukayasa Sukayasa; Muh. Rizal (Mitra Sains, 2017)
The objective of this qualitative research is to find out the description of the critical thinking profile of SMP students in solving mathematic problems in terms of cognitive style. To achieve the objective of this research used Group Embedded Figures Test (GEFT) by dividing students into field dependent and field independent cognitive style, mathematic problem, interview and observation. The result of this research shows that: (1) understanding the problem, SAi and SMd are able to identify, collect and analyse the given facts and information clearly and logicaly, (2) make a plan, SAi dan SMd are able to devine the alternative solution in order to solve the problem (3) carrying out the problem, SAi is able to use the alternative problem solution based on his plan systematically; meanwhile, SMd still finds it difficult to use the alternative problem solution based on his implementation plan not systematically. and (4) in the last step, SAi is able to evaluate the obtained result relevantly. Furthermore, he also can give clear argument in testing the obtained result. Whereas, SMd is not able to evaluate the obtained result relevantly, so he can not the given in testing the obtained result.